HUBUNGAN PENGETAHUAN DENGAN MOTIVASI DALAM MEMBERIKAN BANTUAN HIDUP DASAR KASUS HENTI JANTUNG DI KOMUNITAS BULUTANGKIS - Muin, Ilhamsyah; Pratiwi, Andi Widya (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2024)
Cardiac arrest is a disease of the cardiovascular system and is the number one cause of death in the world and Indonesia. According to WHO data, people died in this case as much as 31 percent of the total deaths from all over the world. This happens in developing countries that have low to moderate income (Widiyono, 2021). This also occurs in the prevalence of events in Indonesia which shows around 37% and it is estimated that around 10 thousand citizens per year will experience this cardiac arrest condition (Riskesdas, 2018). Fast and appropriate management of cardiac arrest events is an indicator of the success of cardiac arrest treatment. Skills that are trained at the beginning of its occurrence both from the general public and health workers can be obtained through training for all levels of society. These trainings will increase knowledge and skills if you get a cardiac arrest. The purpose of this study was to analyze the relationship between knowledge and motivation in providing basic life support in cases of cardiac arrest in the Makassar Badminton Community. This research was conducted using a quantitative, descriptive and cross-sectional approach with the chi-square test relationship analysis. The research sample was 66 respondents. Based on the research results, there is a significant relationship between knowledge and motivation in the management of Basic Life Support in cases of cardiac arrest with a significance level of 0.01 (below 0.05). The conclusion obtained is that the higher a person's knowledge, the higher the motivation to provide assistance in handling Cardiac Arrest in the Badminton sports community and if lack of knowledge causes a person's lack of motivation in providing Cardiac Arrest treatment.